Interferon in the treatment of hairy cell leukemia - Thompson, John A.; Fefer, Alexander (Cancer, 1987)
An ongoing multicenter study has confirmed earlier observations that interferon alfa‐2b (Intron® A, Schering Corp., Kenilworth, NJ) is effective in the treatment of hairy cell leukemia (HCL). The 212 evaluable subjects in this trial received 2 × 106 U/m2 of interferon alfa‐2b subcutaneously, on an outpatient basis, three times a week for 1 year. Of this group, 166 had previously undergone splenectomy, and 94 had received chemotherapy; 96% had more than 50% hairy cells in the bone marrow. Objective responses (complete, partial, and minor) were recorded in 89% of the study group and were characterized by a marked reduction in infections as well as in the need for transfusions. Complete response, defined as a normal complete blood count (CBC) and less than 5% hairy cells in the marrow, was achieved in 4% of the subjects. Partial responses (normal CBC) were attained in 74%, and minor responses (normalization of subnormal hematocrits or granulocyte or platelet counts) in 11%. Normalization of CBC usually did not occur until after 2 to 5 months of therapy. Results were comparable in splenectomized and nonsplenectomized patients. After 1 year of treatment, the responders were randomized to continue therapy for 6 months or to stop treatment and remain under observation. Preliminary findings have shown no significant differences in the incidence or time to progression of disease in the two groups, but additional data will be required before conclusions can be reached with regard to the need for maintenance therapy. Overall, the results of this study indicate that interferon alfa‐2b is well tolerated, produces durable responses, and dramatically improves the quality of life in a high percentage of patients with progressive HCL.